Dynamics of coagulation proteins upon ICU admission and after one year of recovery from COVID-19: a preliminary study - Raquel Behar-Lagares; Ana Virseda-Berdices; Ana Virseda-Berdices; Óscar Martínez-González; Óscar Martínez-González; Óscar Martínez-González; Rafael Blancas; Rafael Blancas; Rafael Blancas; Marcela Homez-Guzmán; Eva Manteiga; Juan Churruca-Sarasqueta; et al. (Frontiers in Cellular and Infection Microbiology)
ObjectivesThis study aimed to investigate the association of baseline coagulation proteins with hospitalization variables in COVID-19 patients admitted to ICU, as well as coagulation system changes after one-year post-discharge, taking into account gender-specific bias in the coagulation profile.MethodsWe conducted a prospective longitudinal study on 49 ICU-admitted COVID-19 patients. Proteins were measured using a Luminex 200™. The association between coagulation protein levels and hospitalization variables was carried out by generalized linear models adjusted by the most relevant covariates.ResultsAt ICU admission, lower factor XII, antithrombin, and protein C levels were linked to the need for invasive mechanical ventilation (IMV) or its duration (p=0.028; p=0.047 and p=0.015, respectively). Likewise, lower factor XII, antithrombin, and prothrombin levels were associated with longer ICU length of stay (ICU LOS) (p=0.045; p=0.022; p=0.036, respectively). From baseline to the end of the follow-up, factor XII, antithrombin, prothrombin, and protein C levels notably increased in patients with longer ICU LOS. One-year post-discharge, differences were found for factor IX, aPTT, and INR. Gender-stratified analysis showed sustained alterations in males.ConclusionsDepleted specific coagulation factors on ICU admission are associated with increased severity in critically ill COVID-19 patients. Most coagulation alterations recover one-year post-discharge, except for factor IX, aPTT and INR, which remain reduced.